2000
DOI: 10.1139/z00-020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of otolith daily increments in the tropical eel Anguilla celebesensis

Abstract: To validate daily increments in otoliths of the tropical freshwater eel Anguilla celebesensis, a time-reference mark was incorporated in the otoliths of glass eels by immersing the eels in alizarin complexone (ALC) solution. They were subsequently reared in aquaria for 10 or 20 days, and the increments outside a fluorescent red ALC mark were counted. The numbers from the 10- and 20-d experiments were 9.4 ± 0.9 (mean ± SD) and 19.4 ± 1.4, respectively, suggesting daily deposition of otolith increments. Precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…Data of Sr and Ca contents around the measurement points were assigned to each 10 growth increments and used for life history transect analysis. Otolith increments of Anguilla japonica (Tsukamoto 1989, Umezawa et al 1989, A. rostrata (Martin 1995) and A. celebesensis (Arai et al 2000a) have been validated as being deposited daily, so we assumed that the species studied here also deposited increments daily. Early life history parameters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data of Sr and Ca contents around the measurement points were assigned to each 10 growth increments and used for life history transect analysis. Otolith increments of Anguilla japonica (Tsukamoto 1989, Umezawa et al 1989, A. rostrata (Martin 1995) and A. celebesensis (Arai et al 2000a) have been validated as being deposited daily, so we assumed that the species studied here also deposited increments daily. Early life history parameters.…”
Section: Methodsmentioning
confidence: 99%
“…The age at deposition of the hatching check was considered as Day 0. The yolk absorption check was the second check outside the central hole, and was visible as a deep dark groove surrounding a crystalline crown just outside the hatch check in A. celebesensis (Arai et al 2000a). The innermost check on the otolith edge was regarded as a freshwater check which was formed when the glass eel entered freshwater (Kawakami et al 1998, Arai et al 1999b.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We assumed that the growth increments in otoliths of Anguilla australis were deposited on a daily basis, as are those of A. japonica, A. rostrata and A. celebesensis, which have been validated (Umezawa et al 1989, Martin 1995, Arai et al 2000. The present study found that the Australiasian eel A. australis took approximately 7 to 9 mo to drift from the spawning grounds to the estuaries of Australia and New Zealand (Table 3), and metamorphosis from leptocephalus to glass eel occurred approximately 5 to 6 mo after hatching.…”
Section: Age Upon Estuarine Arrival In Relation To Otolith Growth Ratmentioning
confidence: 99%